2011
DOI: 10.1007/s11692-011-9130-y
|View full text |Cite
|
Sign up to set email alerts
|

Sympatric Divergence and Performance Trade-Offs of Bluegill Ecomorphs

Abstract: Phenotypic plasticity in response to environmental cues can create distinct morphological types within populations. This variation in form, and potentially function, may be a factor in initiating population divergence and the formation of new species. Here we show the translation of sympatric, habitat-specific morphological divergence into performance differences in energy economy, maneuverability and steady-state locomotion. Littoral and pelagic bluegill sunfish ecomorphs show differences in performance that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 88 publications
3
47
0
Order By: Relevance
“…Accelerations, decelerations and turning rates (Fig. 1C,D) fell within the range measured during sustained flume swimming at an applied average velocity (Plew et al, 2007;Thiem et al, 2015), and were low in comparison to maximal accelerations and angular velocities during maneuvers, which approach 30 m s −2 and 1000 deg s , respectively, in juvenile bass and other centrarchids of similar body mass (Webb, 1978(Webb, , 1986Ellerby and Gerry, 2011). The fish also followed relatively straight paths as indicated by a mean (±s.d.)…”
Section: Resultssupporting
confidence: 64%
“…Accelerations, decelerations and turning rates (Fig. 1C,D) fell within the range measured during sustained flume swimming at an applied average velocity (Plew et al, 2007;Thiem et al, 2015), and were low in comparison to maximal accelerations and angular velocities during maneuvers, which approach 30 m s −2 and 1000 deg s , respectively, in juvenile bass and other centrarchids of similar body mass (Webb, 1978(Webb, , 1986Ellerby and Gerry, 2011). The fish also followed relatively straight paths as indicated by a mean (±s.d.)…”
Section: Resultssupporting
confidence: 64%
“…As such, the observed intraspecific variation in pectoral fin use, swimming cost and U crit could have implications for habitat use in individual fish. For example, Ellerby and Gerry showed that habitat use varies with individual differences in energy economy, steady-state swimming and manoeuvrability in bluegill sunfish (Lepomis macrochirus) (Ellerby and Gerry, 2011). Although P. reticulata often occupy distinct pools in rivers, it remains to be tested whether intraspecific variation in pectoral fin use, swimming cost and U crit influence habitat use within pools and to what degree such relationships (or lack of) affect daily energy expenditures (Careau and Garland, 2012).…”
Section: The Journal Of Experimental Biology 216 (18)mentioning
confidence: 99%
“…We have data on the contributions of each fin to the wake structure during steady swimming locomotion (Drucker and Lauder, 2001;Tytell, 2006). This species has also been used in studies that examined maneuvering behaviors such as escape responses, maneuvering through complex habitats, braking and accelerating, as well as responses to small hydrodynamic perturbations (Drucker and Lauder, 2001;Ellerby and Gerry, 2011;Lauder, 2009, 2013;Higham, 2007;Standen, 2010;Standen and Lauder, 2005;Tytell and Lauder, 2008). The cost of transport for this species has also been show to increase with the gait transition from pectoral fin to caudal fin locomotion (Kendall et al, 2007).…”
Section: Introductionmentioning
confidence: 99%